Pemberdayaan Mustahik melalui Program Balai Ternak Baznas di Kabupaten Pidie Jaya Provinsi Aceh - Fatoni, Ahmad; Utami, Kurnia Dwi Sari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The Livestock Barn Program is a form of community service, especially for the beneficiaries in Pidie Jaya District, Aceh Province. Zakat funds are channeled through the BAZNAS Livestock Barn Program, which is productive with the aim of transforming beneficiaries into benefactors. Through a qualitative descriptive approach, it was found that the main empowerment activities of the BAZNAS Livestock Barn Program include empowering beneficiary farmers through the utilization of productive assets such as livestock and livestock production facilities, initiating and developing farmer institutional businesses, building livestock production centers, and establishing a marketing network for livestock products and their derivatives.